Dinamika Resepsi Santri dalam Praktik Dzikir: Studi Living Qur’an atas Asmaul Husna dan Ayat Dua Puluh di Pesantren Tahfidz - Falasifah Hasyim Chosi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study examines the reception of santri towards the tradition of reciting Asmaul Husna and the 'Twenty Verses' at the Tahfidzul Qur’an Baitul Abidin Darussalam Islamic Boarding School in Wonosobo. This dhikr, performed daily after Maghrib and Fajr prayers, is believed to have spiritual protection and inner tranquility functions. This research aims to describe the dhikr practice, analyze the variations in santri's reception, and explain the influencing factors using Hans Robert Jauss's horizon of expectation theory. A qualitative approach with phenomenological method was employed. Data were collected through participant observation, in-depth interviews with 19 santri, and documentation. The findings reveal three forms of reception: dhikr as spiritual protection (14 santri), dhikr as inner tranquility (3 santri), and dhikr as pesantren obligation (2 santri). Differences in reception are influenced by duration of stay, personal religious experiences, psychological needs, and level of textual understanding. This study contributes to Living Qur’an scholarship by demonstrating that dhikr practices in pesantren are dynamic and subjective, while also proving the adaptability of Jauss's theory for the study of religious practices.